PERTUMBUHAN DAN HASIL DUA VARIETAS BAWANG MERAH (Allium Ascalonicum L.) PADA BERBAGAI JARAK TANAM - Ayu, Neneng Gusti; Rauf, Abdul; Samudin, Sakka (AGROTEKBIS, 2016)
This research aims to determine growth and yield of two varieties of onion (Allium ascalonicum L.) at various distances planting. In addition to determining the appropriate spacing each variety this study used a randomized block design consisting of: (1) two onion varieties; (V1) = Palu valley variety, (V2) Bima variety, (2) distances planting; (J1) 20 cm x 10 cm, (J2) 20 cm x 15 cm, (J3) 20 cm x 20 cm and (J4) 20 cm x 25 cm. The results showed that the onion varietas bima and the valley of the Palu show the response of different growth and production of the spacing tested. Milky red onion varieties produce the number of tubers, plant fresh weight and fresh weight of tuber/clump heavier than valley Varieties Palu. Spacing tenuous (20 cm x 25 cm) increase crop production individually on both varieties tested, but the cumulative spacing narrow (20 cm x 10 cm) higher production. Bima varieties of onion production in the narrow spacing of 7,55 tonnes/ha while the Palu valley varieties of 2,45 tonnes/ha.Â Key Words : Varieties, distances planting.